2019
DOI: 10.1039/c9ce00386j
|View full text |Cite
|
Sign up to set email alerts
|

The role of glass crystallization processes in preparation of high Li-conductive NASICON-type ceramics

Abstract: One of the approaches to tackle the problem of limited electrolyte electrochemical stability, which controls the development of novel electrochemical storage devices, is the use of solid electrolytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…Finally, through DFT calculations, the authors deduced that the addition of Y 2 O 3 changed the concentration of Li ions occupying Li1 and Li3 sites; the increased concentration of Li ions in the Li3 sites had the effect of pushing ions in Li1 sites to other Li3 sites, lowering the hopping energy barrier. Thus, NMR and DFT showed that the introduction of Y 2 O 3 into LAGP led to a denser intergrain microstructure [81], while electron microscopy showed improved grain boundaries, leading to the aforementioned increase in conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, through DFT calculations, the authors deduced that the addition of Y 2 O 3 changed the concentration of Li ions occupying Li1 and Li3 sites; the increased concentration of Li ions in the Li3 sites had the effect of pushing ions in Li1 sites to other Li3 sites, lowering the hopping energy barrier. Thus, NMR and DFT showed that the introduction of Y 2 O 3 into LAGP led to a denser intergrain microstructure [81], while electron microscopy showed improved grain boundaries, leading to the aforementioned increase in conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…A review of the most promising advances in lithium ion NASICON glass-ceramics is summarized in Table . ,,,, ,,,,,,,,,,,,,,, In this table, T g is the glass transition temperature, and T x is the onset for glass crystallization. In summary, using germanium and titanium as B (IV) cation characterize almost all the NASICON glass-ceramics already explored.…”
Section: Lithium Ion-containing Nasicon Glass-ceramicsmentioning
confidence: 99%
“…However, cationic transport is usually limited in these materials. Sulfide glasses present the best transport properties, showing typical lithium conductivity on the order of 10 –3 S cm –1 at room temperature . However, they are very unstable in environmental conditions, generating H 2 S by humidity exposure. , Oxide electrolytes are superior in chemical stability, ion selectivity, and thermal stability compared to polymers and sulfides. ,, In particular, the Na + Super Ionic Conductor (NASICON) is a class of phosphate-type electrolytes that can approach lithium conductivity in the same order of sulfides (10 –4 to 10 –3 S cm –1 ), ,, while the chemical stability in air is maintained. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, despite the superior advantages such as an easy synthesis procedure and low cost, NASICON-based phosphate glass electrolyte materials have not been investigated as a potential solid electrolyte material. 9,10 One of the interesting features of the NASICON-based phosphate materials is that a wide variety of accessible glass compositions with a general formula Na x M y (PO 4 ) 3 , (where M is either a single or combination of tri, tetra, and pentavalent ions), can be prepared to tune the electrochemical and ionic conduction properties. The ionic conductivity (σ = Zeμc) of a material mainly depends on the mobility (μ) and concentration (c) of charge carriers because the charge (e) and valency (Z) of a mobile cation are constant at any temperature.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In the pursuit of NIB development, all the solid-state batteries made by utilizing solid electrolytes for conducting ions have attracted great interest rather than liquid electrolytes because of significant safety concerns. , NASICON (sodium (NA) SuperIonic CONductor)-class materials are offering high chemical stability and Na + -ion mobility. , Because of these superior properties, they are being investigated extensively for their application as electrolyte materials in all solid-state NIBs. Surprisingly, despite the superior advantages such as an easy synthesis procedure and low cost, NASICON-based phosphate glass electrolyte materials have not been investigated as a potential solid electrolyte material. , …”
Section: Introductionmentioning
confidence: 99%